Aniline Sulfonic Acid Induced Uniform Perovskite Film for Large‐Scale Photovoltaics. Issue 9 (15th January 2023) - Wang, Kai‐li; Li, Meng; Lou, Yan‐Hui; Chen, Jing; Shi, Yi‐Ran; Chen, Chun‐Hao; Zhou, Yu‐Hang; Wang, Zhao‐Kui; Liao, Liang‐Sheng
Abstract: Unreacted/excess lead iodide is considered to be the archcriminal for the rapid degradation of hybrid perovskite solar cells. Meanwhile, a high‐quality perovskite film with uniform and large grain size is the basis for high‐performance perovskite modules. Herein, a dual‐site molecular additive 4‐Aniline Sulfonic Acid (4A) is developed to regulate the unreacted/excess PbI2 and passivate defects through hydrogen bonding and intermolecular interactions between amino, and a sulfate groups and PbI2, respectively. Furthermore, the introduction of the 4A additive can induce perovskite seeds to grow uniformly on the substrate, yielding dense, uniform and defect‐less perovskite films with large grain sizes. This enables the fabrication of perovskite photovoltaics with a maximum power conversion efficiency of 24.09% (0.09 cm 2 ) and 20.87% (16 cm 2 ), respectively. This work demonstrated a new strategy to deposit high‐quality large‐scale perovskite films for photovoltaic modules. Abstract : Aniline sulfonic acid with dual sites is utilized to cure excess/unreacted lead iodide in perovskite films. The introduction of additives can induce a uniform growth of perovskite seeds on the substrate, which aids the growth of high‐quality and uniform perovskite films. The fabricated perovskite photovoltaics deliver maximum power conversion efficiency of 24.09% (0.09 cm 2 ) and 20.87% (16 cm 2 ), respectively.